Eosinophils as predictive biomarkers in anti-programmed cell death 1 monotherapy for non-small cell lung cancer - Uchida, Takahiro; Nakagome, Kazuyuki; Hashimoto, Kosuke; Iemura, Hidetoshi; Shiko, Yuki; Mouri, Atsuto; Yamaguchi, Ou; Uchida, Yoshitaka; Nagai, Yoshiaki; Soma, Tomoyuki; Kaira, Kyoichi; Nagata, Makoto; et al. (Frontiers in Immunology, 2025)
BackgroundThe relationship between eosinophilia and cancer development has recently been investigated. However, the role of eosinophils in tumor immunity, particularly in the context of immune checkpoint inhibitor (ICI) therapy, remains poorly understood.MethodsWe investigated the relationship between peripheral blood eosinophil and T-lymphocyte subsets and the clinical characteristics of patients undergoing anti-programmed cell death-1 (PD-1) monotherapy for non-small cell lung cancer (NSCLC). The study included 204 patients treated with nivolumab monotherapy, and clinical data and treatment responses were recorded. PBMCs were collected from 44 out of 204 patients before treatment to analyze T-lymphocyte subsets, focusing on their correlation with blood eosinophils.ResultsThe percentage of blood eosinophils before nivolumab treatment was positively correlated with the percentage of effector memory subsets in both CD4+ (r = 0.43, p = 0.0045) and CD8+ T cells (r = 0.35, p = 0.020). It was negatively correlated with the percentage of naïve subsets of CD4+ T cells and positively correlated with the percentage of inducible T cell co-stimulator cells among CD8+ T cells. Patients with higher eosinophil levels (≥1.7%) before nivolumab treatment exhibited significantly longer progression-free survival (log-rank p = 0.014) and overall survival (log-rank p = 0.001) than those with lower eosinophil levels. An early increase in the eosinophil count after treatment was also associated with a better response to nivolumab.ConclusionHigher blood eosinophil levels may indicate activated T-cell immunity and may be a promising biomarker for the efficacy of anti-PD-1 monotherapy in patients with NSCLC.